THE REPRESENTATION OF SOCIAL ACTIONS IN OBAMA'S 2010 NATIONAL SECURITY STRATEGY: A CRITICAL DISCOURSE ANALYSIS OF OBAMA'S ACTIONS TOWARD TERRORISM - Yully Yudantari Saputri, - (2012)
Focusing on the representation of social actions, the study aims to reveal the actions attributed to each actor in Barack Obama's 2010 National Security Strategy. It investigates the kinds, distribution, and tendency of those actions. The present study applies Van Leeuwen's framework of discourse as the recontextualization of social practice (2008); his social action network is used to characterize each social action. The analysis shows that there are six main actors in the discourse investigated with 227 actions and 27 reactions attributed to them. The actions of Obama's administration, the main actor, regarding terrorism are distributed in the form of 159 material and 7 semiotic actions. The study also finds that there are two actions that tend to be deactivated and three actions that tend to be abstracted. The first kind of deactivation is the nominalized objectivation of the names of social practice as a whole ("terrorism," "attack,"and "partnership."). The affective reactions of the administration and Americans are also deactivated. With regard to the tendency of abstraction, the data shows that the social action "attack" tends to be generalized; the actions of Al-Qa'ida and the Taliban are abstracted by the label of ability; and the positive actions carried by the administration are also abstracted. The tendency of the representation of these actions suggests that the administration uses these as the legitimation of what it does in the effort of defeating Al-Qa'ida and other violent extremists.